(untitled) (Fiep Bulletin - online, 2011)
Introduction: Excess body fat has a direct relationship with some conditions harmful to health. According to the literature a good level of fitness can bring many benefits to the health of an individual, and to prevent hypokinetic diseases, which are related to sedentary lifestyle. The population with intellectual deficit (DI) requires data to establish these correlations. Objective: To compare body composition and physical activity levels in adults athletes and nonathletes with ID. Method: The selected sample of 16 young adult male, mean age 26.5 + -2.10, and 8 that only physical activity at school (I) and 8 participants (P) of competition at least two years, all Race participants of 5 and 10 kilometers in the city of Brasilia. Body composition was evaluated BMI, WHR and percentage of fat (% BF) was measured by skinfold caliper (Cescorf) 7 folds in the second protocol Pollock: subscapular, triceps, pectoral, axillary, abdominal and femoral medium. The level of physical activity by questionnaire self-administered IPAQ. Descriptive statistics (mean and standard deviation) was used and the t test studente to discuss the results. The significance level was set at p <0.05. Results: We observed that several parameters are different from the NA group as for group A and fat percentage reached values (0.05 and .04) respectively.Conclusion: Although a study with a small number of participants and a high standard deviation for one of the groups observed that levels of moderate to vigorous physical activity are related to body fat rates corresponding to rates recommended in both groups.